Social Investment Funds in Sweden: Status and Design Issues - Hultkrantz, Lars; Vimefall, Elin (Scandinavian Journal of Public Administration, 2017)
Long-term investments in individual and social human capital such as preschool, school, family support, early-intervention for youth at risk and other programmes that are part of the welfare services provided by local government in Sweden are generally managed with one-year-ahead budget planning. In the light of criticism that the resulting resource alloca- tion is biased due to short-sightedness, silo mentality and risk aversion, in recent years more than a fifth of Swedish municipalities have established “social investment funds” for pro- moting investment and innovation views on such measures. This article provides a background on the motives and current status of these funds at the national level and describes in more detail the design and project funding in two cases. Two critical design issues are discussed; whether investment returns should be paid back to the fund and whether assess- ment should be made of societal benefits other than costs avoided.